Favourable multi‐institutional experience with penoscrotal decompression for prolonged ischaemic priapism. (31st July 2020) - Baumgarten, Adam S.; VanDyke, Maia E.; Yi, Yooni A.; Keith, Christopher G.; Fuchs, Joceline S.; Ortiz, Nicolas M.; Cordon, Billy H.; Pagliara, Travis J.; Ward, Ellen E.; Jaderlund, John W.; Teeple, Charles S.; Christine, Brian S.; et al.
Abstract : Objectives: To report our multi‐institutional experience using penoscrotal decompression (PSD) for the surgical treatment of prolonged ischaemic priapism (PIP). Materials and Methods: We retrospectively reviewed clinical records for patients with PIP treated with PSD between 2017 and 2020. Priapisms were confirmed as ischaemic based on clinical presentations and cavernosal blood gas abnormalities. Treatment with irrigation and injection of α‐agonists in all patients had failed prior to PSD. Patient characteristics, peri‐operative variables and outcomes, and changes in International Index of Erectile Function (IIEF) scores were evaluated. Results: We analysed 25 patients who underwent a total of 27 PSD procedures. The mean duration of priapism at initial presentation was 71.0 h. Irrigations and injections in all patients had failed, while corporoglanular shunt treatment in 48.0% of patients (12/25) had also failed prior to PSD. Of the 10 patients who underwent unilateral PSD, two (20.0%) had priapism recurrence. Both were treated with bilateral PSD, with prompt and lasting detumescence. Among the 15 patients undergoing primary bilateral PSD, none had priapism recurrence. Of the 15 patients with documented sexual function status at last follow‐up, nine (60%) reported spontaneous erectile function adequate for penetration, while six (40%) reported erectile dysfunction. The median (interquartile range) decrease in IIEF‐5 score was 3.5 (0–6.75) points after PSD. Two patients underwent uneventful inflatable penile prosthesis placement following PSD. Conclusions: Penoscrotal decompression presents a simple, safe, highly effective and easily reproducible procedure for resolution of PIP. PSD should be considered as a viable salvage or alternative strategy to corporoglanular shunt procedures.